Picture Dictionary Augmented Reality based for Pre-School Children's Learning - Rusyaidi; Muhammad Asyraf Abdullah Zawawi; Salini Krishna Pillai (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
The use of technology in education has shown that technology can increase motivation in learning. This study will highlight the Augmented Reality Application For Picture Dictionary For Pre-School Children’s Learning. The objective of this study is to design application features that can make children interested in knowing the content found in the picture dictionary and test the usability and functionality of applications that children can use. This research was conducted using the ADDIE design model based on five phases namely analysis phase, design phase, development phase, implementation phase and testing phase. These five phases are described in detail in the methodology component of the study. This study was analyzed through a descriptive study which is a type of quantitative study involving 20 children. Children’s acceptance of the developed Augmented Reality (AR) application was assessed by answering a questionnaire with the help of a teacher. The results show that the developed AR applications work well and can attract children to learn.